Sex-differences in Mothers' own milk and neurodevelopmental outcomes in preterm infants - Zhao, Tingting; Li, Aolan; Chang, Xiaolin; Xu, Wanli; Quinn, Tyler; Chen, Jie; Matson, Adam P.; Chen, Ming-Hui; Taylor, Sarah N.; Cong, Xiaomei (Frontiers in Pediatrics, 2025)
ObjectiveTo identify sex-specific feeding patterns and associations with growth and neurodevelopment in preterm infants during NICU through 2 years of corrected age (CA).MethodsA cohort study was conducted with 216 preterm infants (gestational age 28 0/7 to 32 0/7 weeks). Daily feeding regimens, including mother's own milk (MOM), human donor milk, and formula; daily growth; acute and chronic pain/stress were documented during NICU. NICU Network Neurobehavioral Scale (NNNS) (36 to 38 postmenstrual age), and Bayley Scales of Infant and Toddler Development (Bayley) Edition III (1 and 2 years of CA) were measured.ResultsBetween week 9 to 16 after birth, only females showed a positive association between growth z-score and proportion of MOM intake before week 8 (p < 0.05). Sex-differentiated associations between MOM and stress were observed (p < 0.05). MOM proportion was positively correlated with language or cognitive scores at 2 years of CA in females (p = 0.01), this correlation not evident in males.ConclusionsWe discovered a sex-specific “window of opportunity” for feeding, growth and risk predictors for neurodevelopment up to 2 years of CA. These insights may inform development of tailored feeding regimens, potentially mitigating growth and development differences observed between males and females.